The role of strategic knowledge towards formulating business strategy in MSC status companies: a preliminary outlook / Norzanah Mat Noor and Siti Sakinah Ab. Rahim - Mat Noor, Norzanah; Ab. Rahim, Siti Sakinah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This is a preliminary study on examining the relationship between Knowledge Management (KM) and Competitive Intelligence (CI) that might be integrated as a management approach to leverage strategic knowledge which impacts Business Strategy Formulation (BSF). The literature revealed that it becomes managerial challenges when competitive advantage is seen as an association with the creation, transfer, and use of knowledge for value creation of organisations. The purpose of this study is to validate developed instruments that examining the relationship between KM, CI and BSF. Data were collected using an online questionnaire sent to a total of 30 representatives from the management team members of MSC Status Companies in Malaysia. From the analysis using SPSS, the results showed a positive significant positive relationship between strategic knowledge and business strategy formulation. Specifically, KM showed strong impacts on business strategy formulation, as compared to CI. The findings of this preliminary study begin to fill a research gap by empirically prove and support the idea that strategic knowledge is the core organisational asset for business strategy formulation that will lead organisations to gain competitive positions.